Poorly Differentiated Breast Adenocarcinoma as a Rare Cause of Right Ventricular Outflow Tract Compression: Case Report and Review of the Literature. (May 2020) - Long, Ashleigh; Marik, Paul
Metastatic cancer that involves the structures of the heart is a rare complication and most commonly diagnosed during postmortem examination. Classically, the development of secondary tumors involves invasion of the pericardium or the myocardium and may disrupt the cardiac conduction system, causing new arrhythmias and heart failure. In this article, we present the case of a 58-year-old female with new diagnosis of ventricular bigeminy, and evidence of cardiac tamponade physiology from direct compression of the right ventricular outflow tract from high-grade carcinoma of the left breast. As oncologic therapies advance and provide more life-prolonging options to patients, recognition of the mass effect of large tumors should be recognized.